Numerical Analysis of Thermo-Elasto-Plastic Problems - Kleiber, M.; Niezgoda, T. (Engineering Transactions, 1988)
The purpose of this paper is to present the theoretical and numerical background adopted in the course of the development of the computer program TEMAS (Thermo-Mechanical Analysis of Structures). The paper demonstrates the effectiveness of the finite element analysis in predicting the behaviour of inelastic materials subjected to mechanical and thermal loadings. A number of computational examples illustrate the paper.